Conceptualizing and operationalizing 'inclusive' talent management: four different approaches - Cadigan, Francoise; Dries, Nicky; Zelderen, Anand van (My University, 2023)
In this chapter, we identify four different approaches to inclusive TM - a concept that is increasingly advocated for by both academics and practitioners but has so far lacked clarity and actionability. The four approaches are (1) focusing on potential and strengths rather than talent and gifts, (2) increasing the size of the talent pool, (3) defining a broader range of talent domains, and (4) topgrading the entire organization. We propose that exclusive and inclusive TM (co-)exist on a continuum rather than as dichotomies and develop a decision tree for organizations and researchers to determine which custom approach might best fit their talent philosophy.
Keywords: inclusive talent management; exclusive talent management; potential; high potentials; star performers; strengths